Social Work Students' Awareness And Knowledge of Domestic Violence - Noor Azizah Ahmad; Nabisah Ibrahim; Nurul Nabilah Ramli (Asian Social Work Journal, 2022)
Malaysians are frequently exposed to information about the problem of domestic violence, which affects children, women, the elderly, and maids. In order to address this issue, it is critical to increase the knowledge, awareness, and involvement of community members of all ages. To that end, a study was conducted to determine students' level of awareness and knowledge about important aspects of domestic violence, such as the provision of policies, rights, and available assistance channelled through various organisations to victims of violence. This quantitative study collected data by distributing a set of questionnaires. The study surveyed 132 Social Work students in their first through fourth years at one of Malaysia's public universities. The students were chosen because they are most likely to work in social service organisations after graduation. Descriptive statistics was used to determine social work students’ level of awareness and knowledge about domestic violence. The findings indicated that respondents had a moderate level of awareness regarding domestic violence. Meanwhile, their awareness of the Domestic Violence Act's provisions, rights, and available assistance services for victims of domestic violence was limited. The findings of this study demonstrate a lack of awareness and understanding among Social Work students regarding domestic violence. There were a few respondents who retained gender-stereotypical beliefs toward domestic violence victims and perpetrators. Thus, it is proposed that extended awareness and practical training programmes concerning domestic violence be provided through a comprehensive educational syllabus to assist students in increasing their level of awareness and understanding about domestic violence. This is hoped to increase students' readiness and ability to deal with domestic violence cases in their professional endeavours.